Complicaciones asociadas a tratamientos ortodónticos en adolescentes - Solis Velasco, Pamela Cristina (2023)
ABSTRACT: Complications associated with orthodontic treatments in adolescents are caused by the changes they generate in the oral cavity when undergoing this treatment, and there are various complications that are associated with both dental pieces and adjacent tissues. This bibliographic review was developed with the aim of analyzing the main complications associated with orthodontic treatment in adolescents and its action on the dental pieces and adjacent tissues. The project was carried out based on a bibliographic review of scientific articles obtained from databases such as SAGE, Scielo, ResearchGate, Science direct and MDPI, which were obtained systematically through the analysis of variables taking into account the inclusion and exclusion criteria, as well as the fact that the articles comply with the ACC greater than 1.5 and the SJR impact factor, so 64 articles were obtained and worked on in this bibliographic review. After the analysis of the scientific articles, it was found that the complications associated with orthodontic treatments are mostly associated with oral hygiene due to the increase of bacterial biofilm, thus producing pathologies. Therefore, the main complications associated with orthodontic treatments in adolescents are gingival hyperplasia, gingival recessions, external inflammatory root resorptions, white spot lesions and pain.